Subcutaneous advanced glycation end products, cardiovascular risk factors and vascular health during childhood development in a Swiss population - Hauser, Christoph; Lona, Giulia; Köchli, Sabrina; Streese, Lukas; Infanger, Denis; Faude, Oliver; Hanssen, Henner (Frontiers in Physiology, 2024)
Background: Skin-derived advanced glycation end products (sAGEs) have been associated with cardiovascular (CV) risk and mortality in adults. We hypothesize that cardiorespiratory fitness (CRF), body mass index (BMI) and vascular health are associated with development of sAGEs during childhood.In our prospective cohort study, 1171 children aged 6 to 8 years were screened for sAGEs, BMI, retinal arteriolar diameters (CRAE) and pulse wave velocity (PWV), using standardized procedures. To determine CRF a 20m shuttle run was performed. After four 4 years, all parameters were assessed in 675 children using the same protocols.: Higher initial CRF levels were significantly associated with lower sAGEs (β [95 CI] -0.02 [-0.03 to -0.002] au, p=0.022) levels at follow-up, although they showed a greater change from baseline to follow-up (β [95 CI] 0.02 [0.002 to 0.03] au, p=0.027). Moreover, individuals with higher sAGEs at baseline showed narrower CRAE (β [95% CI] -5.42 [-8.76 to -2.08] μm, p= 0.001) at follow-up and showed a greater change in CRAE (β [95% CI] -3.99 [-7.03 to -0.96] μm, p= 0.010) from baseline to follow-up. Conclusions: Exercise and higher CRF may help mitigate the formation of AGEs during childhood, thereby reducing the risk for development of CV disease associated with AGEsinduced damage. Preventive strategies may need to target CRF early in life to achieve improvement of CV risk factors and may counteract the development of CV disease later in life.